The results of selection of mixed germ-plasm corn (Zea mays L.) among self-pollinated families S4 for the duration of the «sprouting–flowering of 50% of ears» period - О. Л. Гайдаш (Plant Varieties Studying and Protection)
The results of evaluation and selection of breeding material of mixed germ-plasm corn for early ripeness among self-pollinated families S4 by the length of the «sprouting–flowering of 50% of ears» period are given. A signifi cant infl uence of weather conditions during the years of study on the length of this indicator was determined. Response of studied corn test-crosses on growing conditions are described. Self-pollinated families DK22282111, DK28211111, DK21511111, DK20192321, DK26143111 were singled out which had a high tolerance to growing conditions and stable «sprouting–flowering of 50% of ears» period.